Predictors of protean career and the moderating role of career strategies among professionals in Malaysian Electrical and Electronics (E&E) industry - Siew, Chin Wong; Mohd Rasdi, Roziah (Emerald Group Publishing Limited, 2015)
Purpose– The purpose of this paper is to examine the effects of individually related variables and the moderating role of career strategies on protean career among professionals in Malaysian Electrical & Electronics (E & E) industry.